Analysis of serum markers of cellular immune activation in patients with bullous pemphigoid. Issue 12 (15th August 2017) - Bieber, Katja; Ernst, Anna Lara; Tukaj, Stefan; Holtsche, Maike M.; Schmidt, Enno; Zillikens, Detlef; Ludwig, Ralf J.; Kasperkiewicz, Michael
Abstract: Experimental models of bullous pemphigoid (BP), the most frequent subepidermal autoimmune bullous disease, revealed that the immune response leading to blister formation represents an incompletely understood complex process involving different inflammatory cells. In contrast to previous reports commonly focusing on limited molecular and cellular phenotypes of the disease, the aim of this study was to investigate a broad spectrum of markers of cellular immune activation in patients with BP. We found that serum levels of soluble CD4, myeloperoxidase, S100A12, eosinophil cationic protein and soluble P‐selectin were significantly elevated in patients with active BP compared with normal controls. Mast cell tryptase and neopterin serum levels significantly decreased at the time of clinical remission of the patients. Additionally, serum concentrations of soluble IL‐2 receptor, mast cell tryptase and soluble P‐selectin were significantly associated with levels of circulating anti‐BP180 autoantibodies. Our findings confirm and extend previous reports suggesting some concomitant involvement of a panel of molecules representative for a wide spectrum of cellular players (T cells, mast cells, neutrophils, eosinophils, macrophages and platelets) orchestrating the inflammatory reaction in BP. These data may favour the employment of broad‐spectrum or combined immunosuppressants, potentially together with an anticoagulant treatment, over cell‐ or molecule‐specific targeted therapy in patients with this disorder.